Do we need antiplatelet therapy in thrombocytosis? Pro - Alberio, Lorenzo (Hämostaseologie, 2016)
Thrombocytosis (defined as platelets >450 × 109/l) has several aetiologies. After having excluded spurious thrombocytosis (e. g., due to microspherocytes, schistocytes, cryoglobulins, or bacteria), the differential diagnosis of true thrombocytosis encompasses secondary causes (as diverse as inflammation, infection, malignancy, iron deficiency, or asplenia), primary hereditary (rare forms of familial thrombocytosis) and primary acquired entities (either in the context of a myelodys-plastic syndrome or more frequently a myeloproliferative neoplasia). This manuscript addresses the following aspects: 1) diagnostic approach to thrombocytosis; 2) various mechanisms leading to a high platelet count; 3) potential of some of these mechanisms to modulate platelet function, producing hyper-reactive platelets and thus exerting a direct impact on the thrombotic risk; 4) indication of anti-thrombotic treatment in patients with thrombocytosis. There is a single prospective randomized clinical trial showing the benefit of acetyl-salicylic acid in polycythaemia vera. For other types of primary thrombocytosis and for secondary forms, treatment decisions have to be individualized according to the patient thrombotic and bleeding risks, taking into account the mechanism causing thrombocytosis. This manuscript discusses experimental and clinical data suggesting that besides patients with essential thrombocythaemia and other forms of primary thrombocytosis also those with thrombocytosis in the context of chronic inflammation, malignancy, or exposure to high altitude might benefit from anti-platelet treatment.
Keywords: Thrombocytosis; hyper-reactive platelets; thrombotic risk; mechanisms